Hubungan Fear of Missing out dengan Social Media Addiction pada Pengguna Instagram - Salim, Ahmad; Jatnika, Ratna; Yudiana, Whisnu (Jurnal Ilmu Siber dan Teknologi Digital, 2023)
Purpose: This study aims to see the relationship between fear of missing out and social media addiction among students of the Faculty of Psychology, Padjadjaran University who use Instagram. Methodology/approach: Researchers used the fear of missing out scale (FoMOS) and the Bergen social media addiction scale (BSMAs) to measure the two variables. This research is a quantitative study using a non-experimental correlational study design. The sample collected was 94 people using stratified sampling technique which was divided into four strata (batch 2017, 2018, 2019, 2020). The Spearman test was conducted to see the correlation between the two variables. Results/findings: The results obtained show a significant correlation between the two variables with a positive relationship. This shows that the higher the level of anxiety (FoMO) of an individual, the higher the tendency for the individual to show addictive behavior towards social media (SMA), Instagram. Limitations: The limitation of this research lies in the number of participants, as the researchers were unable to study a broader population. Contribution: This research contributes to our understanding of the relationship between fear of missing out and social media addiction and provides valuable insights for promoting responsible social media usage.